2013
DOI: 10.1177/0002716213497452
|View full text |Cite
|
Sign up to set email alerts
|

Wealth Disparities Before and After the Great Recession

Abstract: The collapse of the labor, housing, and stock markets beginning in 2007 created unprecedented challenges for American families. This study examines disparities in wealth holdings leading up to the Great Recession and during the first years of the recovery. All socioeconomic groups experienced declines in wealth following the recession, with higher wealth families experiencing larger absolute declines. In percentage terms, however, the declines were greater for less-advantaged groups as measured by minority sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
168
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(178 citation statements)
references
References 21 publications
7
168
0
3
Order By: Relevance
“…Specifically, they found that net worth of the top 50 wealthiest Americans fell by 17% from 2008-2009, while it fell 37% among the top 1% wealthiest households (Wolff et al 2011: 150). Consistent with this finding, Frank (2013) High quality research has already documented trends in inequality with the recession (e.g., Emmons and Noeth 2012;Pfeffer et al 2013;Shapiro et al 2013;Friedline et al 2014). …”
Section: Inequality and Economic Recessionsmentioning
confidence: 85%
See 2 more Smart Citations
“…Specifically, they found that net worth of the top 50 wealthiest Americans fell by 17% from 2008-2009, while it fell 37% among the top 1% wealthiest households (Wolff et al 2011: 150). Consistent with this finding, Frank (2013) High quality research has already documented trends in inequality with the recession (e.g., Emmons and Noeth 2012;Pfeffer et al 2013;Shapiro et al 2013;Friedline et al 2014). …”
Section: Inequality and Economic Recessionsmentioning
confidence: 85%
“…More recent research has suggested the Great Recession further increased inequality along a variety of dimensions, including wealth, income, age, race, and education (Emmons and Noeth 2012;Pfeffer et al 2013;Shapiro et al 2013;Friedline et al 2014). For example, using PSID data, Pfeffer and colleagues (2013) found that low income and minority households with relatively low levels of education lost a higher proportion of their wealth than others.…”
Section: Inequality and Economic Recessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of people living below the poverty line, as measured by the US census, 6. There have also been changes in the wealth inequality (Pfeffer et al 2013;Wolff 2013). For example, between 2007 and 2011 about one-fourth of families lost more than 75 percent of their wealth and about half lost more than 25 percent of their wealth.…”
Section: Povertymentioning
confidence: 99%
“…1 Large differences in wealth remain even after controlling for confounding factors such as earnings or family structure (Choudhury 2001;Barsky et al, 2002;Altonji and Doraszelski, 2005). The racial wealth gap has persisted over time, and the Great Recession widened it to the highest level in 30 years (Pfeffer, 2013;Kocchar and Fry, 2014). Possible explanations for this wealth gap include differential saving behavior, asset composition, and bequest motives (Smith, 1995;Menchik and Jianakoplos, 1997;Choudhury, 2001;Even and Macpherson, 2003;Gittleman and Wolff, 2004;Kocchar and Fry, 2014;Kuan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%